DEVELOPMENT OF RENEWABLE ENERGY: THE EXPERIENCE OF EAST GERMANY FOR UKRAINE - FREYER, Eckhard; LISHCHYNSKYY, Ihor; LYZUN, Mariia (Journal of European Economy, 2021)
Renewable energy development has become a modern global priority. German regions are characterized by a very high degree of renewable energy development. In 2020, the volume of electricity generation from renewable sources exceeded the traditional ones. However, the use of renewable energy sources in the transport sector and in the heating / cooling industry remains relatively low in Germany. Regions in the East Germany had historically been dominated by coal energy. Staring with 2017, the EU has begun implementing a policy of developing so-called «Coal Regions in Transition», aimed at supporting economic diversification and technological transformation of coal and carbonintensive regions. A total of 42 such regions were identified, including 4 in East Germany. The natural environment of the East Germany fits the development of wind energy better, though the solar system could be considered a substitute for the current coal plants. The green energy sector in Ukraine is only emerging. However, renewable energy is attracting more attention and investments. Its share in total supply has risen from 1.7 percent in 2007 to almost 5 percent in 2019. The energy of biofuels and waste is dominating among the renewable sources, comprising around 77 percent of their total supply. The paper aims to reveal the experience of East Germany to enhance the mechanism of green energy development in Ukraine. Among the new recommended tools for Ukrainian practice are export-credit agencies, EPC-contractors, green securities, and environmental investments. JEL: F29, Q20, Q32, Q42, Q48.